PENGARUH MODEL PEMBELAJARAN DAN KECERDASAN EMOSIONAL TERHADAP KEMAMPUAN MENULIS CERITA FABEL PADA SISWA KELAS VIII SMP DI KABUPATEN NGAWI - Nur Dwi Sukmono; St. Y. Slamet; Edy Tri Sulistyo (Universitas Sebelas Maret, 2017)
The purpose of this study is to know (1) Differences in the ability to write fables between students who subjected to Jigsaw learning model and learning model PBL; (2) Differences in the ability to write fables between students who have high emotional intelligence and low emotional intelligence; (3) Interaction between the learning model and the emotional intelligence of the ability to write fables.This research was conducted in July 2016 - January 2017 at the Junior High School in eight class of 2016/2017 school years. Sampling techniques using Cluster Random Sampling. Research method used is the quasi-experiment. Data collection technique used performance tests and questionnaires closed. The validity test of test performance using the construct validity was reliability using ratings. Validity test of the questionnaire enclosed using the product moment while reliability using Cronbach alpha. Analyzed using ANOVA two lines because the table shows the 2 X 2 factorial.The results of this research after the balance test and test prerequisite is (1) there are differences in the ability to write fables between students who subjected to Jigsaw learning model and PBL learning model; (2) there are differences in the ability to write fables between students who have high emotional intelligence and Low emotional intelligence; (3) there are interaction between the learning model and the emotional intelligence of the ability to write fables.